The voice of the child in parental divorce: implications for clinical practice and mental health practitioners. Issue 2 (4th May 2017) - Brand, Carrie; Howcroft, Greg; Hoelson, Christopher Norman
Abstract : Objective: Research on parental divorce suggests that the nature of the divorce process, as experienced by the child, is the most important factor in his or her post-divorce adjustment. Research regarding children's experiences of the divorce process has been limited and the adult perspective has dominated the discourse on divorce; only recently has research started to consider children's viewpoint. This article describes a narrative inquiry into the experiences and perceptions of parental divorce, of 9- to 10-year-old children. Its aim is to use children's stories of parental divorce to inform the practice of professionals working with such children. Method: The research adopted a narrative paradigm. Unstructured interviews were conducted with five children whose parents were divorced. Data were analysed thematically. Findings: Seven themes were identified. The first theme explored children's endeavours to describe and explain parental divorce. An additional six themes were developed around the types of stories children told of the divorce process. The seven themes were: (i) What is a divorcement; (ii) Stories of loss; (iii) Stories of gain; (iv) Stories of change; (v) Stories of stability; (vi) Healing stories; and (vii) Complicating stories. Conclusion: On the basis of the narratives elicited from children on parental divorce, this article proposes several guidelines for professionals such as psychologists, registered counsellors, social workers, and teachers as well as parents in their possible interventions with children. Some guidelines may also be of use to family and maintenance courts, and the government departments of health and education.